2022
DOI: 10.1021/acsestengg.1c00392
|View full text |Cite
|
Sign up to set email alerts
|

Square-Wave Alternating Voltage for Enhancing Cr(VI) Reduction in a Carbon Fiber-Based Flow-Through Electrode System

Abstract: Electrochemical reduction with a flow-through electrode system (FES) has been regarded as an effective method for water decontamination. However, under a direct voltage (DV) power supply, the reduction efficiencies were strongly limited by the gas bubbles generated in porous electrodes and the electrostatic repulsion between the negatively charged pollutants and cathode. Herein, square-wave alternating voltages (SWAV) were applied to regulate the anodic−cathodic polarities of electrodes for eliminating the gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A recent study also demonstrated that the Cr( vi ) reduction efficiency increased to 86% at square-wave alternating voltages as compared with 20–30% at the direct voltage, using a flow-through electrode system with the double carbon fiber felt. 50 These results demonstrate that the combination of the pulsed voltage with the pseudocapacitive electrode ( e.g. PANI) was suitable for continuous operation to achieve a high Cr( vi ) reduction efficiency.…”
Section: Resultsmentioning
confidence: 69%
“…A recent study also demonstrated that the Cr( vi ) reduction efficiency increased to 86% at square-wave alternating voltages as compared with 20–30% at the direct voltage, using a flow-through electrode system with the double carbon fiber felt. 50 These results demonstrate that the combination of the pulsed voltage with the pseudocapacitive electrode ( e.g. PANI) was suitable for continuous operation to achieve a high Cr( vi ) reduction efficiency.…”
Section: Resultsmentioning
confidence: 69%
“…Titanium rods were used to connect the anode and cathode with an adjustable DC power supply (DG1718E-5), and a piece of quantitative filter paper was put between the electrodes to avoid short circuit problems. Based on our previous work, 21 the synthetic Cr( vi ) solution was first oxidized by the CFF anode, then Cr( vi ) was reduced to Cr( iii ) by the cathodes, and finally discharged from the water collector using a peristaltic pump.…”
Section: Methodsmentioning
confidence: 99%